Angiotensin-(1-7) and Mas receptor in the brain - Rukavina Mikusic, Natalia Lucía (2021)
The renin-angiotensin system (RAS) is a key regulator of blood pressure and electrolyte homeostasis. Besides its importance as regulator of the cardiovascular function, the RAS has also been associated to the modulation of higher brain functions, including cognition, memory, depression and anxiety. For many years, angiotensin II (Ang II) has been considered the major bioactive component of the RAS. However, the existence of many other biologically active RAS components has currently been recognized, with similar, opposite, or distinct effects to those exerted by Ang II. Today, it is considered that the RAS is primarily constituted by two opposite arms. The pressor arm is composed by Ang II and the Ang II type 1 (AT1) receptor (AT1R), which mediates the vasoconstrictor, proliferative, hypertensive, oxidative and pro-inflammatory effects of the RAS. The depressor arm is mainly composed by Ang-(1-7), its Mas receptor (MasR) which mediates the depressor, vasodilatory, antiproliferative, antioxidant and anti-inflammatory effects of Ang-(1-7) and the AT2 receptor (AT2R), which opposes to the effects mediated by AT1R activation. Central Ang-(1-7) is implicated in the control of the cardiovascular function, thus participating in the regulation of blood pressure. Ang-(1-7) also exerts neuroprotective actions through MasR activation by opposing to the harmful effects of the Ang II/AT1R axis. This review is focused on the expression and regulation of the Ang-(1-7)/MasR axis in the brain, its main neuroprotective effects and the evidence regarding its involvement in the pathophysiology of several diseases at cardiovascular and neurological level.